Evaluation of interconnection of special working capacity and response of single combat sportsmen`s cardiorespiratory system at the stage of direct training for competition - Kiprych, S.; Donets, O.; Komosenko, O.; Khomenko, P.; Zhamardiy, V.; Shkola, O.; Binetskyi, D.; Kasich, N.; Serhiienko, V.; Bloshchynskyi, I. (International Journal of Applied Exercise Physiology, 2020)
In the article the interconnection between special working capacity and the response of single combat sportsmen`s cardiorespiratory system at the stage of direct training for competitions is analyzed. To solve the set tasks, the following methods were used: the method of analysis and generalization of literature, pedagogical experiment, methods of mathematical statistics. The pedagogical experiment involved the use of the chronodynamometer method, the instrument of which was the impact dynamometer of M. P. Savchyn`s «Spuderg». With the help of this device the level of special working capacity of qualified single combat sportsmen was determined. In particular, using the «8 s» test, indirect determination of creatine and phosphate anaerobic working capacity was performed; using the «40 s» test, special high speedendurance (indirect determination of glycolytic anaerobic working capacity) was tested; «3x3» test (3 rounds for 3 minutes each with one minute break between rounds), during which the maximum amount of heavy punches should be performed, was used to identify the power mode of single combat sportsmen. To evaluate the response of the cardiorespiratory system (CRS) and to compare the response rates of athletes the running exercises were simulated on the treadmill at a standard speed of 3.0 m/s. As a result of the calculation of the multiple correlation coefficient, the interconnection of speed deployment and resilience response of the CRS on the working capacity of athletes (Creatine Phosphate Capacity Index, Glycolytic Capacity Index, Integral Index of Speed-Power Readiness, the number and power of punches` total capacity during the test), was established. The results of the investigation showed that the result of the multiple correlation coefficient (R) was within the limits of 0.64-0.76; even higher were the results of multiple correlation interconnections of indicators of speed deployment and reaction renewal (R = 0.81-0.91), indicators of reaction resilience (R = 0.83-0.90) on indicators of working capacity.